2004
DOI: 10.1086/380509
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Resistance in a Double‐Blind Study Comparing Lopinavir/Ritonavir Plus Stavudine and Lamivudine to Nelfinavir plus Stavudine and Lamivudine

Abstract: Study M98-863 was a double-blind, randomized, phase 3 study that compared lopinavir/ritonavir with nelfinavir, each coadministered with stavudine and lamivudine, in 653 antiretroviral therapy-naive human immunodeficiency virus (HIV) type 1-infected subjects. The incidence of HIV drug resistance was analyzed using baseline and rebound virus isolates from subjects with plasma HIV RNA >400 copies/mL from weeks 24 to 108 of therapy. No evidence of genotypic or phenotypic resistance to lopinavir/ritonavir, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 31 publications
11
159
3
Order By: Relevance
“…Our finding reinforces the concept that ongoing viral replications [26] and few treatment options are associated with an increased probability of disease progression [27]. It has been reported that the use of boosted protease inhibitors (Boosted PI) is associated with multiple clinical benefits, including higher efficacy against resistant HIV strains [28], lower rates of resistance emergence at highadherence levels [29] and a lack of PI-associated resistance mutations after virologic failure in treatment-naïve patients [30]. As well, studies have shown that Boosted PI offers a marginal independent protective effect on disease progression [23,31].…”
Section: Discussionsupporting
confidence: 86%
“…Our finding reinforces the concept that ongoing viral replications [26] and few treatment options are associated with an increased probability of disease progression [27]. It has been reported that the use of boosted protease inhibitors (Boosted PI) is associated with multiple clinical benefits, including higher efficacy against resistant HIV strains [28], lower rates of resistance emergence at highadherence levels [29] and a lack of PI-associated resistance mutations after virologic failure in treatment-naïve patients [30]. As well, studies have shown that Boosted PI offers a marginal independent protective effect on disease progression [23,31].…”
Section: Discussionsupporting
confidence: 86%
“…Traditionally, PIs are drugs characterized by a high genetic barrier to resistance [37][38][39], and thus generally associated with a lower emergence of drug resistance at virological failure [39][40][41]. For this reason, they are preferentially used in patients with high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Complicating these decisions is the relative paucity of data regarding the rate at which anti-retroviral resistance develops after the onset of virologic treatment failure in patients receiving highly active anti-retroviral therapy (HAART). [25][26][27] The purpose of this study was to define the time to accrual of genotypic resistance mutations, particularly thymidine analogue mutations (TAMs) and major protease inhibitor mutations, in persons with a persistently detectable plasma viral load (pVL) despite being on a stable antiretroviral regimen. We also sought to evaluate the impact of co-administration of lamivudine on the emergence of TAMs given the detrimental effect of the 184V mutation on HIV replication capacity, especially in combination with TAMs.…”
mentioning
confidence: 99%